(3CSQGQ GdJShjb GdESJQGJjLj (B/s - (3Gdabj, EHQGgjes ((3eUQ (B: s (3HOGjI ddGfJGL hGdfTQ hGdJhRjY(B;(3OGQ GdhSjW ddWHGYI hGdfTQ hGdJhRjY(B, s, 2014)
(3jVe eGgh GdJShjb, eGPG JYfj GdegGQGJ GdTNUjI, bhGfjf GdYbd GdHGWf hJCKjQgG aj GdJShjb, OjfGejcjI GdJcjja GdYUHj, GdJShjb GdESJQGJjLj, bhGfjf GdJShjb, CfhGY GdJShjb, LPhQ GdJShjb GdGSJQGJjLj, GdJShjb GdGSJQGJjLj GdeNJdW, JUeje GdeWHhYGJ hGdOYGjI , GdJShjb GdeHGTQ dZI GdMjGI GdeSJbHdjI, GdeRjL GdJShjbj, EOGQI eRjL GdefJLGJ(B.s
Keywords: (3GdJShjbs